ANALISIS PENERAPAN SISTEM DENDA PEMBIAYAAN MURABAHAH PADA PT. BANK SYARI’AH MANDIRI CABANG DUMAI - Dedy Rachmad (Inovbiz: Jurnal Inovasi Bisnis, 2016)
Abstract: Murabahah funding at syari’ah banking is the transaction selling buy where the bank to mention the price of goods and the number of profit. The bank act as a seller while customer as a buyer. This study attemp to analyse the fines implementationof murabahah funding in particular motorists on the Bank Syari’ah Mandiri (BSM)branches Dumai. The results of the kind showsthat the system fines murabahah funding motor vehicles that implemented BSM in accor- dance with the concept of Dewan Syari’ah Nasional Majelis Ulama Indonesia (DSN MUI), but does not comply with the legal verdict Fiqih Islam that take shelter under Munazzamah Mu’tamar al-Islami. Key words: The Fine System, Murabahah Funding